2019
DOI: 10.1089/zeb.2018.1691
|View full text |Cite
|
Sign up to set email alerts
|

Early Transition to Microdiets Improves Growth, Reproductive Performance and Reduces Skeletal Anomalies in Zebrafish (Danio rerio)

Abstract: Zebrafish is a model species with a high variability of feeding regimes among fish facilities. The use of live feeds for early life stages is a common practice, and few studies have focused early weaning into microdiets. The lack of standardized feeding protocols among research facilities promotes discrepancies in biological performances, and few studies relate dietary regimes to zebrafish development. The objective of this work was to assess the effect of an early transition into microdiets in zebrafish devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 55 publications
(105 reference statements)
1
29
0
Order By: Relevance
“…To our knowledge, in the only existing relevant study, Martins et al. (2019) demonstrated that the early transition from Artemia nauplii to microdiets significantly reduces vertebral abnormalities in zebrafish (from 90% to ca 50%).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…To our knowledge, in the only existing relevant study, Martins et al. (2019) demonstrated that the early transition from Artemia nauplii to microdiets significantly reduces vertebral abnormalities in zebrafish (from 90% to ca 50%).…”
Section: Introductionmentioning
confidence: 92%
“…Zebrafish is a valuable model species for developmental biology and genetics, fish biology, ecotoxicology, neurophysiology and biomedicine (Bhagat et al., 2020; Lieschke & Currie, 2007; Patterson & Parichy, 2019; Spence et al., 2008), including human skeletal pathology with respect to genetic disorders (Boswell & Ciruna, 2017; Gistelinck et al., 2018). Despite the significance of husbandry conditions for the normal skeleton development of this species, existing relevant literature is scarce (Martini et al., 2021; Martins et al., 2019; Printzi et al., 2021). Understudying the importance of nutrition for fish biological performance, as well as for zebrafish maintenance cost and easiness, different studies target on establishing larval feeding protocols mainly for fast growth, high survival rates and improved reproduction capacity (Carvalho et al., 2006; Delomas & Dabrowski, 2019; Gomez‐Requeni et al., 2010; Kaushik et al., 2011; Lawrence et al., 2015; Önal & Langdon, 2000), but rarely for normal skeletal development (Martins et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observation that most of the 6-dpf larvae exposed to 10 µg/L of cadmium are also bended, and that the incidence of skeletal deformities is much higher in larvae exposed for longer periods to lower concentrations, suggest that cadmium also affects zebrafish skeletal development. It is worth mentioning that the incidence of deformities observed in the control group (56%) is within the normal range (45-65%) for wild-type zebrafish [35][36][37]. The presence of spinal deformities has already been reported in zebrafish larvae exposed to cadmium [38] but also in larvae of European carp Cyprinus carpio [39], Australian crimson spotted rainbow fish Melanotaenia fluviatilis [40], red seabream Pagrus major [41], Japanese medaka Oryzias latipes [42], Soldatov's catfish Silurus soldatovi [43], and in juvenile mosquitofish Gambusia affinis [44].…”
Section: Discussionmentioning
confidence: 62%